SOME PROBLEMS OF TEACHING A SECOND FOREIGN LANGUAGE - Suyarova Mavjuda Ergashevna (Western European Studies, 2024)
The article discusses some problems of teaching a second foreign language in the context of the principle of variability in Education system of Uzbekistan in connection with the need to develop in students certain competencies that allow them to participate in a new society built on knowledge. A set of problems associated with teaching and learning a second foreign language is discussed, and ways to solve them are proposed
Keywords: Education; second foreign language; English language; principle of variability